Clarisas y dominicas. Modelos de implantación, filiación, promoción y devoción en la Península Ibérica, Cerdeña, Nápoles y Sicilia - Garì, Blanca; COLESANTI, Gemma Teresa; Jornet-Benito, Núria (Reti Medievali E-Book, 2017)
The volume is the result of the research project Claustra. Atlas of female spirituality. The book deals with the analysis of the religious landscape marked by the communities of the Poor Clares and Dominicans nuns. The investigation of the territorial structure of the various kingdoms takes place through five paths: knowledge of poorly studied areas in female monastic topography; understanding of foundational dynamics and the role of communities of religious mulieres; the dynamics of the urban layout and the processes of communication and action that created the monastic landscape; the importance of patronage and female sponsorship in foundational models and cultural promotion; the analysis of devotional practices and the material culture of communities in a functional, spatial and performative context. El presente volumen es el resultado de la investigación del proyecto Claustra. Atlas de espiritualidad femenina. El libro se ocupa del análisis del paisaje religioso marcado por las comunidades de clarisas y dominicas. Desde una estructura territorial por reinos se abordan cinco lineas: el conocimiento de áreas poco estudiadas en la topografía monástica femenina; la comprensión de dinámicas fundacionales y el papel de grupos de mulieres religiosae; la dinámica de implantación urbana y los procesos de interacción creadores de paisaje monástico; la importancia del mecenazgo y patronazgo femenino en los modelos fundacionales y de promoción cultural; el análisis de las prácticas devocionales y la cultura material de las monasterios femeninos en un contexto funcional, espacial y performativo.